Bioprocessing of Mulberry Leaf Juice With High-GABA Producing Lactobacillus plantarum: A Strategy for Flavor, GABA Enrichment, and Antioxidant Enhancement - Xie J; Yang S; Matia-Merino L; Chen J; Tian HS (John Wiley and Sons Ltd on behalf of the Institute of Food Technologists, 2026)
The purpose of this work is to isolate γ-aminobutyric acid (GABA)-producing lactic acid bacteria (LAB) from traditional Chinese pickles and to evaluate their fermentation characteristics and functional effects in a mulberry leaf juice system. Six GABA-producing strains were isolated, comprising five Lactobacillus plantarum strains and one Enterococcus faecium strain. These strains demonstrated significant probiotic properties, exhibiting traits such as acid tolerance, bile salt resistance, in vitro gastrointestinal resistance, cell surface hydrophobicity, auto-aggregation, γ-hemolysis, and antibiotic sensitivity. The GABA content in fermented mulberry leaf juice ranged from 0.663 ± 0.007 to 0.879 ± 0.023 mg/mL, which was 9.61 to 12.74 times that of the initial content. Mulberry leaf juice's flavor, α-glucosidase inhibitory activity, DPPH and hydroxyl radical scavenging capacity, and ferric-reducing antioxidant power (FRAP) were all greatly improved by the LAB fermentation. A quality evaluation model for fermented mulberry leaf juice was developed using principal component analysis (PCA), identifying L. plantarum L10 as the optimal probiotic strain for fermentation.
Keywords: lactic acid bacteria (LAB); mulberry leaf; principal component analysis (PCA); probiotic properties; γ‐aminobutyric acid (GABA); Morus; Lactiplantibacillus plantarum; gamma-Aminobutyric Acid; Fermentation; Antioxidants; Plant Leaves; Fruit and Vegetable Juices; Probiotics; Taste; Flavoring Agents